Drug Abuse in the Young Generation: Law Enforcement Challenges (Comparative Study of Indonesia and Australia) (Journal of Creativity Student, 2022)
Drug abuse that occurs is mostly carried out by the younger generation starting from their teens, this is due to the fact that teenagers are a period where humans are very vulnerable and easily influenced by various bad influences from their circle, drug abuse is one of the, and as if it has been addressed by them as a trend in this modern era. Drugs can cause addiction effects for users, and on this basis they will try their best to get and use them again. This problem is supported by students’ access to various resources where they have their own pocket money and very broad association. Meanwhile, narcotics abuse itself is one of the crimes that can cause a lot of damage which is regulated in a special law, namely Law Number 35 of 2009 concerning Narcotics. This law was drafted to eradicate narcotics criminals and regulates criminal sanctions that can be given to them and the parties involved in their distribution, this is necessary considering the massive impact that this dangerous substance can have.